The art and architecture of academic writing - Prinz, Patricia (John Benjamins Publishing Company, 2021)
"This book is a bridge to confident academic writing for advanced non-native English users. It emphasizes depth over breadth through mastery of core writing competencies and strategies which apply to most academic disciplines and genres. Tailored to students in EMI programs, the content was piloted and revised during a longitudinal writing study. The innovative approach prepares students to write for the academic community through the dual lenses of Art (developing a writer's voice through choices in language, style, and topics) and Architecture (mastering norms of academic language, genre, and organization.) The user-friendly text maximizes time for writing practice and production by avoiding lengthy readings. Part 1 builds skills and confidence in writing by focusing on assignments that do not require research. Part 2 applies newly mastered principles, skills, and strategies to research-based writing. Students learn to incorporate thesis, research, and evidence into a process for academic writing by following the AWARE framework (Arranging to write, Writing, Assessing, Revising, and Editing.)"--